Indicators for Media Pluralism in the Member States - (:unkn) unknown (My University, 2025)
The present study forms part of the European Commission’s three-step approach for advancing the debate on media pluralism within the European Union. The approach was launched in January 2007 with a Commission Staff Working Paper and is planned to result in a Commission Communication on media pluralism at the end of 2009 or beginning of 2010. The objective of the study was to develop a monitoring tool for assessing risks for media pluralism in the EU Member States and identifying threats to such pluralism based on a set of indicators, covering pertinent legal, economic and socio-cultural considerations. The Final Report describes the approach and method used to design these indicators and their integration into a risk-based framework. The outcome of this study is a prototype for a Media Pluralism Monitor – a risk-based, holistic, user-friendly and evolving monitoring tool that includes indicators of a legal, economic and socio-demographic nature. In order to account for the multi-faceted character of media pluralism, these indicators relate to various risk domains, including media ownership and/or control, media types and genres, political pluralism, cultural pluralism and geographic pluralism. Furthermore, they cover the various stages of the media value chain: supply, distribution and use. The Monitor offers a diagnostic, not a prescriptive tool on the basis of established risk management strategies. Its purpose is to facilitate the collection of empirical data on various risks for media pluralism given the particular economic, sociodemographic and legal situation in each Member State. The MPM aids users by providing them with a tool for auditing media pluralism that highlights areas of current and potential risk and allows for the comparison of situations and responses adopted. It is designed to accommodate the diverging profiles of media landscapes throughout the EU by considering differences in market size, media development, cultural and regulatory traditions, and takes into account the impact that underlying realities such as population size and average income levels have on the level of media pluralism sustainable by commercial means.
Keywords: Media pluralism; economic indicators; media concentration